Antimicrobial effect of Sargassum plagiophyllum mediated gold nanoparticles on Escherichia coli and Salmonella typhi. (July 2020) - Dhas, T. Stalin; Sowmiya, P.; Kumar, V. Ganesh; Ravi, M.; Suthindhiran, K.; Borgio, J. Francis; Narendrakumar, G.; Kumar, V. Ramesh; Karthick, V.; Kumar, C.M. Vineeth
Abstract: Biosynthesis of gold nanoparticles has been carried out with various sources like bacteria, plants and algae. Seaweeds have high nutritional and medicinal properties. Sargassum plagiophyllum is seaweed that has excellent antioxidant activity. This study aims at evaluating the antimicrobial activity of biosynthesize d gold nanoparticles from the extract of S. plagiophyllum. The synthesised nanoparticles were subjected to characterization studies and the mean particle size was found to be 65.87 nm. The biosynthesised gold nanoparticles were treated with gram negative bacteria Escherichia coli (ATCC 25922) and Salmonella typhi (ATCC 6539) and the antibacterial activity was studied using epifluorescence microscopy, atomic force microscopy (AFM) and Field emission Scanning electron microscopy (FE–SEM). The synthesised nanoparticles cause significant amount of deterioration to bacterial cells, when examined using microscopic and cell viability analysis.